Transition to the circular economy: the story of four case companies. Issue 11 (2nd June 2020) - van Loon, Patricia; Van Wassenhove, Luk N.
Abstract : Shifting from a linear sales model to a circular service-based business model is far from straightforward. Many challenges accrue in the transition process, including finding the right market for the recirculated product/service, setting up the reverse supply chain, selecting the right partners, and making sure the new business model is sustainable in the short, medium and long term. This paper discusses the challenges of four companies trying to close the loop while preserving current profit levels. It describes their initial ideas on how the circular business model should be designed, the process they went through, challenges faced, and the eventual outcome. Based on the learnings of the four case companies, we summarise recommendations about preparatory steps required before making the transition towards a circular business model.